(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Higher education may once again be at a crossroad with the racial climate in the United States and what that means for college campuses. Consequently, institutions of higher education must commit to ensuring a supportive organizational structure for the social and psychosocial well-being of Black students and guaranteeing support resources for the psychological well-being of Black students. Such efforts require significant and enduring structural changes within institutions of higher education that should be ongoing and consistent.